PENANAMAN MANGROVE UNTUK PEMULIHAN EKOSISTEM PANTAI WABABE NEGERI TULEHU - Sukirno, Pradina Anjarwaty; Sitania, Safinah Yulianty (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mangrove ecosystems are the main focus of the Indonesian government for conservation and restoration activities. Damage to the mangrove ecosystem has suffered quite apprehensive damage due to the actions of irresponsible parties. The function of the mangrove ecosystem, which incidentally is a source of life for other living things, is starting to shift. This also affects human life, especially those living in coastal areas. The restoration of the mangrove ecosystem in Tulehu Village aims to restore damaged mangrove areas on the coast of Wababe Beach. The implementation of the mangrove planting involved youth, the Trash Hero Ambon Community, Lecturers at the Tual State Fisheries Polytechnic, as well as Lecturers and Students at the Muhammadiyah University of Maluku. Collaboration with related agencies (BPDAS Waehapu Batumerah) was also carried out to obtain mangrove seedlings. The planting of this mangrove sapling is expected to be able to restore the ecological function of mangroves and raise public awareness to protect the environment around the coast of Tulehu Village.